Novel organic doped inorganic photosensors - Yakuphanoğlu, Fahrettin; Mensah-Darkwa, Kwadwo; Al-Ghamdi, Ahmed A.; Gupta, R. K.; Farooq, W. A. (Elsevier, 2016)
Coumarin doped CdSe/p-Si diodes were prepared to obtain new photodiodes for optoelectronic applications. The chemical composition of Cd and Se in CdSe and coumarin samples was confirmed by EDX spectrum. Using FE-SEM analysis, it was observed that the particle sizes of coumarin doped CdSe composites were changed with coumarin. The forward bias current of the diodes increase exponentially with voltage for all diodes studied exhibiting rectification behavior. The obtained m value indicates that the diodes exhibited a linear photocurrent behavior. The photosensitivity plot of Log (I-PH) vs. Log (P) yielded an average in of 1.24. The device with 0.03% coumarin doping level showed the best performance such as lowest ideality factor, highest current density. We have evaluated that the fabricated diodes could be used as an optical sensor in various optoelectronic applications. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Sol-gel coating; Solar energy materials; Photodiode; Coumarin; CdSe; Schottky